Eosinophilic esophagitis during sublingual and oral allergen immunotherapy. Issue 4 (August 2019) - Cafone, Joseph; Capucilli, Peter; Hill, David A.; Spergel, Jonathan M.
Abstract : Purpose of review: The aim of this review is to discuss the current evidence regarding the development of eosinophilic esophagitis (EoE) in individuals undergoing oral and sublingual immunotherapy (SLIT) for both food and environmental allergens. Cumulative incidence of EoE in patients on allergen immunotherapy for peanut, milk, and egg is estimated. Recent findings: De novo development of EoE in patients undergoing oral and SLIT has been demonstrated on the scale of case reports and prospective randomized trials. However, few individuals with EoE-like symptoms during immunotherapy undergo endoscopy, and the long-term outcomes of immunotherapy-associated EoE are unknown. Summary: Evidence exists to suggest that allergen immunotherapy could place individuals at risk for the development of EoE, the true incidence of which may vary depending on antigen exposure and methods used to define the condition.